Aliased tidal signatures in continuous GPS height time series - Penna, Nigel; Stewart, Michael (American Geophysical Union AGU, 2003)
Coordinate time series are often derived from continuous GPS data processed as discrete 24 hour solutions. Under this regimen, residual semi-diurnal and diurnal crustal tide signatures are under-sampled, resulting in aliased periodic signals in the coordinate time series. A secondary aliasing effect, well known from satellite altimetry studies but generally ignored in GPS analysis, arises from the repeat period of the satellite orbits being longer than the Nyquist period of the semi-diurnal and diurnal tidal signatures. This paper derives the theoretical periods for these two aliasing effects for the principal semi-diurnal and diurnal tidal constituents. The presence of both types of aliased signals in GPS time series is then demonstrated using simulated GPS data and also considered for time series derived from real GPS data. It is shown that the beating of the two aliased signals invariably results in spurious signatures in the time series with semi-annual and annual periods.